The other me - Jeng, Sarah Zachrich (Berkley, 2021)
"Perfect for fans of Russian Doll and Dark Matter--an edge-of-your-seat story of a failed artist who, on her twenty-ninth birthday, accidentally opens a door to an alternate reality where she never pursued her dreams and must uncover the forces behind the switch before time runs out. On her twenty-ninth birthday, Chicago artist Kelly steps through a door at a gallery opening and emerges in her Michigan hometown. Suddenly her life is unrecognizable: She's got twelve years of the wrong memories in her head and she's married to Eric, a man she barely knew in high school. Racing to get back to her old life, Kelly's search leads only to more questions. In this life, she loves Eric and wants to trust him, but everything she discovers about him--including a connection to a mysterious tech startup--tells her she shouldn't. And strange things keep happening. The tattoos she had when she was an artist briefly reappear on her skin, she remembers fights with Eric that he says never happened, and her relationships with loved ones both new and familiar seem to change without warning. But the closer Kelly gets to putting the pieces together, the more her reality seems to shift. And if she can't figure out what happened on her birthday, the next change could cost her everything.."--